Diversity of mobile genetic elements in carbapenem-resistant Enterobacterales isolated from the intensive care units of a tertiary care hospital in Northeast India - Mitra, Shravani; Naha, Sharmi; Chakraborty, Joy; De, Subhadeep; Kaur, Harpreet; Majumdar, Tapan; Basu, Sulagna (Frontiers in Microbiology, 2025)
IntroductionMobile genetic elements (MGEs) play a crucial role in the spread of carbapenem resistance. A study was undertaken to characterize MGEs and evaluate their contribution to the spread of carbapenem resistance in Escherichia coli and Klebsiella pneumoniae collected from three intensive care units (ICUs) of a tertiary care hospital in Tripura.MethodsIsolates were subjected to susceptibility testing, genotypic detection of carbapenemases and their transmissibility, whole-genome sequencing (WGS), and phylogenomic analysis.ResultsE. coli and K. pneumoniae were the dominant Enterobacterales, exhibiting resistance to the majority of antibiotics. WGS of carbapenemase-producing E. coli (n = 15/48,31%) and K. pneumoniae (n = 13/26,50%) revealed the presence of blaNDM-1,5,7 (n = 21), blaKPC-2 (n = 1), and blaOXA-181,232 (n = 8). Isolates were diverse and belonged to different sequence types, including epidemic clones (K. pneumoniae-ST16/101/147/231; E. coli-ST167/410/648). This study has noted the allelic shift of blaNDM-1 to blaNDM-5 similar to global reports. blaNDM-1,5,7-bearing plasmids were conjugative but those carrying blaKPC-2 and blaOXA-181,232 were non-conjugative. blaNDM-1,5,7 were present in diverse replicons: IncF-types (predominant), IncHI1B, IncX3, and IncX4, etc., while blaOXA-181,232 were present in ColKP3, corroborating with global studies. blaNDM-1,5 was associated with intact/truncated ISAba125 in Tn125, blaNDM-7 with IS3000, blaKPC-2 with ISKpn6, and ISKpn7 in Tn4401b, and blaOXA-181,232 with ∆ISEcp1 in Tn2013, depicting an ancestral genetic context noted globally. Study isolates were related to other Indian isolates, primarily from blood.DiscussionThe association with different MGEs noted in the study is similar to those in other parts of India and the globe, signifying that the genetic determinants are part of the global gene pool. These associations can facilitate the spread of carbapenem resistance, leading to outbreaks and treatment failures.